Knowledge is power in four dimensions : models to forecast future paradigm : with artificial intelligence integration in energy and other use cases /: models to forecast future paradigm : with artificial intelligence integration in energy and other use cases. (2022) - Zohuri, Bahman; Mossavar-Rahmani, Farhang, 1947-; Behgounia, Farahnaz
No abstract available